The Implementation of Mind Mapping Technique in Teaching Students Speaking Skills at 7th Grade in EFL Classroom in One Junior High School in Pabedilan - Siti Sarah; Ikariya Sugesti; Eline Rozaliya Winarto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2021)
This study aims to determine the application of mind mapping techniques in teaching speaking at 7th grade IN EFL CLASSROOM IN ONE JUNIOR HIGH SCHOOL IN PABEDILAN. The object of research is only focused on the learning process, while the subject of this research is the English teacher at the school. During the learning activities carried out in 2 observations and 4 meetings. The first meeting only observed the teacher applying mind mapping in the speaking class. After the second meeting, the researcher prepared an observation checklist to find out how the teacher applied the mind mapping. The third meeting was an interview with the teacher concerned and the last meeting confirmed the results of data processing in several previous meetings while saying goodbye. This study used qualitative research methods. Data collection techniques include observation, interviews and documentation. In the introduction, the researcher observed the teacher teaching process and then proceeded to the next meeting. Based on the data obtained from observations, it can be seen that the application of mind mapping techniques applied by English teacher so far is quite good, because the techniques used by the teacher are in accordance with the theory proposed by Buzan (2004). The results of the interviews showed that the obstacles in the learning process using mind mapping techniques were on the students themselves. Not all students have the same learning style, some are fast, medium and slow. Therefore, they often have to take different ways to understand the same information or course.